The sanford guide to HIV/AIDS therapy 2010 - Sanford, Jay P.; Sande, Merle A.; Gilbert, David N.; Moellering, Robert C.; Eliopoulos, George M. (USA : Antimicrobial therapy, 2010)
Como complejidades de la atención aumenta, este libro ofrece una gran cantidad de información emergentes, las referencias apropiadas y directrices racionales para la atención. El alcance se ha ampliado para incluir más información relevante para la atención del SIDA en el mundo en desarrollo.
Table 1 Assessment of HIV infection Risks & recommendations for HIV testing Figure 1 Natural history of HIV Table 2 Initial Evaluation of HIV-infected adult patient Table 3A Laboratory diagnosis of HIV infection antibody tests, western blot confirmation & HIV RNA quantitation. Figure 2 Life cycle of HIV with sites of action of antiretrovirals Table 3b CD4/CD8 T-lymphocyte counts in HIV patients Más otros títulos....
Incluye índice
Keywords: VIH; SIDA; INFECCIONES POR VIH; ENFERMEDADES INMUNOLOGICAS